2011
DOI: 10.1242/dev.069930
|View full text |Cite
|
Sign up to set email alerts
|

The cytoskeletal regulator Genghis khan is required for columnar target specificity in theDrosophilavisual system

Abstract: SUMMARYA defining characteristic of neuronal cell type is the growth of axons and dendrites into specific layers and columns of the brain. Although differences in cell surface receptors and adhesion molecules are known to cause differences in synaptic specificity, differences in downstream signaling mechanisms that determine cell type-appropriate targeting patterns are unknown. Using a forward genetic screen in Drosophila, we identify the GTPase effector Genghis khan (Gek) as playing a crucial role in the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…2a ). Strikingly, differentiating photoreceptors displayed active Myosin caps at the apical cortex, which were not formed in cells mutant for gek /MRCK 25 ( Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a ). Strikingly, differentiating photoreceptors displayed active Myosin caps at the apical cortex, which were not formed in cells mutant for gek /MRCK 25 ( Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Flies were maintained at 25°C on standard food. To generate whole mutant eyes, the EGUF/GMRhid system was used 45 in combination with the gek NP5192 and gek omb1080 alleles 25 . Canton S flies were used as control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed that afferent-afferent interactions among R axon growth cones of the same fascicle mediate their specific lateral directions during cartridge selection [6], [9], [17], [27], [31], [34], [35], [36]. However, Gogo is not mediating afferent-afferent interactions between R1–R6 growth cones as loss of Gogo in single R cells does not affect target cartridge selection.…”
Section: Discussionmentioning
confidence: 99%
“…The actin cytoskeleton is also linked to presynaptic assembly, as disruption of F-actin in C. elegans can affect presynaptic assembly in vivo [77 • ] (Figure 3b). In the Drosophila visual system, the cytoskeletal regulatory protein Ghengis Khan (GEK) is required for columnar targeting specificity [78 • ]. The actin cytoskeleton underlies other neurodevelopmental programs besides synaptic specificity, including morphogenesis, cell migration and guidance.…”
Section: Beyond the Homophilic Interaction: Matching Levels Of Receptmentioning
confidence: 99%